Mapping Cyber Law and Drone Research Trends: A Data Analysis - Wulandari, Shofia Eka Putri; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This study involved a multi-step data retrieval process from Lens.org, aimed at analyzing the landscape of cyber law and drone research. The primary objective was to conduct a literature review on the intersection of cyber law and drone technology, and it was undertaken as part of a coursework requirement on Cyber Law. The data collection process involved searching for articles related to "Cyber Law" or "Cyberlaw" and "Drone," resulting in a dataset of 6,563 records. Subsequent filtering narrowed it down to 3,899 journal articles, and a further filter focusing on the subject matter "Law" yielded 455 articles. The final stage involved analyzing various aspects of the dataset, including top institutions, trends over time, active authors, fields of study, countries/regions, and publishers. This data offers valuable insights into the legal aspects of drone technology in the context of cyber law and can serve as a comprehensive resource for researchers, journalists, and students seeking information on this subject. Moreover, the dataset's reusability allows for further exploration and analysis, contributing to an ongoing understanding of this dynamic field.Highlight: Comprehensive Dataset: A dataset of 6,563 records encompassing cyber law and drone technology research, providing a holistic view of this evolving legal domain. Valuable Insights: Data analysis reveals top institutions, active authors, influential publishers, and research trends, offering critical insights into the field's dynamics. Reusable Resource: The dataset's reusability makes it a valuable tool for ongoing research, journalism, and academic exploration of cyber law's implications in the world of drones. Keywords: Cyber Law, Drone Technology, Data Analysis, Legal Insights, Research Trends